METROLOGICAL MODELING AS A BASIS OF MEASUREMENT TECHNIQUE DESIGN AND IMPLEMENTATION - S. S. Sokolovsky; D. V. Solomakho; B. V. Tsitovitch (Приборы и методы измерений)
The article describes the use of modeling in measurements and control, which can be regarded as “metrological modeling” of the measurement objects, measuring process and measuring techniques in general. Metrological simulation allows to estimate the projected errors of measurement procedures and techniques to optimize the measuring control design stage.